Sistema multimedia interactivo para mejorar el proceso de enseñanza- aprendizaje del idioma kichwa en la unidad educativa" San Juan de Ilumán". - Otavalo, Rosa D. (2022)
This article is focused on making known the importance of incorporating information and communication technology tools in the educational environment, either in classrooms or outside of them, because they can significantly strengthen the teaching process learning the Kichwa language, for which it has been proposed to implement an interactive multimedia system designed under the parameters of the bilingual intercultural knowledge system, for which it was considered essential to include teachings of grammar, orality, community and specific cultural practices that students use internalize their dialogues and linguistic domains to achieve a good level of fluency on the parameters mentioned about the Kichwa language. Keywords: Online education, digital tools, teaching-learning.